Strategic sectors and essential jobs: A new taxonomy based on employment multipliers - Lorenzo Cresti; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
In this paper we propose a novel sectoral taxonomy integrating three different attributes of sectors, namely i) the strategic dimension reflected into their belonging to different classes of the Pavitt taxonomy, ii) the capacity to create jobs both internally and externally with respect to their sector/country, iii) the essentiality in satisfying basic needs. To accomplish the task we rely on the World Input-Output Tables and on the Socio-Economic Accounts database (Timmer et al., 2015) to build vertically integrated sectoral employment multipliers and we focus on Italy as a case study, a country which has undergone a deep structural transformation in the last twenty years, loosing productive capacity and also employment potential. The period of investigation goes from 2000 until 2014. We validate the patterns against other selected OECD countries. We finally propose an agenda for industrial policies identifying three specific sectors of intervention for the State, namely the pharmaceutical, the automotive and the care sectors.
Keywords: J21; L6; O14; O25; 330; Input-output; industrial policy; productive structure; employment dynamics; care sectors